2011
DOI: 10.5194/acp-11-1671-2011
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the East Asian summer monsoon on long-term variations in the acidity of summer precipitation in Central China

Abstract: Abstract. The acidity of precipitation has been observed at stations of the Acid Rain Monitoring Network run by the China Meteorological Administration (CMA-ARMN) since 1992. Previous studies have shown that different long-term trends exist in different regions but detailed analysis of the causes of these is lacking. In this paper, we analyze summertime precipitation acidity data from the CMA-ARMN during 1992-2006 using EOFs and show that the summertime pH in China had different trends before and after 2000. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Nevertheless, in order to improve the knowledge on acid rain and resulting effects in China, a great need still persists for better control of the environmental degradations. Based on the latest 15 years observations (1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006) of the acid rain network, statistics and analysis results showed that the acid rain still dominated in the vast regions south of the Yangtze River, with an obvious expanding tendency of acid rain zones in central and northern China where alkaline dust from the desert areas, cement production, and construction activities largely neutralized the acids in the past (Annual report of CAMS, 2009;Xie et al, 2009;Tang et al, 2010;Ge et al, 2011). More recently, acid deposition rate in Northeast China strongly increased since 2004, especially in Liaoning Province identified as one of the most affected areas (Hong et al, 2009;Yang et al, 2012a;Zhang et al, 2012;The Liaoning Environmental Bulletin Report in 2007: http://www.lnepb.gov.cn/zfxxgk/hjzl/hjzlzkgb/201011/t201 01111_19082.html).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, in order to improve the knowledge on acid rain and resulting effects in China, a great need still persists for better control of the environmental degradations. Based on the latest 15 years observations (1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006) of the acid rain network, statistics and analysis results showed that the acid rain still dominated in the vast regions south of the Yangtze River, with an obvious expanding tendency of acid rain zones in central and northern China where alkaline dust from the desert areas, cement production, and construction activities largely neutralized the acids in the past (Annual report of CAMS, 2009;Xie et al, 2009;Tang et al, 2010;Ge et al, 2011). More recently, acid deposition rate in Northeast China strongly increased since 2004, especially in Liaoning Province identified as one of the most affected areas (Hong et al, 2009;Yang et al, 2012a;Zhang et al, 2012;The Liaoning Environmental Bulletin Report in 2007: http://www.lnepb.gov.cn/zfxxgk/hjzl/hjzlzkgb/201011/t201 01111_19082.html).…”
Section: Introductionmentioning
confidence: 99%
“…Tai, and two typical mega cities suffering severe acid rain -Chongqing and Guangzhou -are also marked in the left-hand figure. The topographical map was derived from the Microsoft ® Encarta ® 2009Encarta ® © 1993Encarta ® -2008 central China (Larssen et al, 2006;Huang et al, 2008;Wang and Xu, 2009;Xie et al, 2009;Tang et al, 2010;Ge et al, 2011). Beijing is located out of the traditional regions impacted by acid rain in China.…”
Section: Introductionmentioning
confidence: 99%
“…Also, latitudinal and longitudinal cross sections show a northward shift of the spherical aerosol plume attributable to the summer monsoon. Ge et al (2011) reported that strong East Asian summer monsoon has caused lower acidity of summer precipitation in Central China. As illustrated in Fig.…”
Section: Seasonal Variations Of the Vertical Profiles And Horizontal mentioning
confidence: 99%